(untitled) (Research, Society and Development, 2022)
The theme addressed in this investigation aims to analyze the issue of education and its relationship with work in Simone Weil who dedicated his life to the equality of the working class. The research starts from a guiding question as the pedagogical method called “translation”, proposed by this philosopher, for the education of workers and peasants in the early twentieth century: this method can be applied to the teaching of philosophy in public schools in Brazil in the days of today? This research is characterized as a bibliographic review, which was carried out in the Google Scholar database. It is significant to emphasize that the teaching of philosophy proved to be something important for education, since for students it is necessary to point out a different, reflective and critical view of philosophy, as did Weil and other thinkers, that is, the translation of philosophical speech in order to facilitate students’ learning.